2011
DOI: 10.1016/j.urology.2010.05.055
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Stricture Management Among Male Medicare Beneficiaries: Underuse of Urethroplasty?

Abstract: Objectives We sought to analyze trends in male urethral stricture management through the use of 1992–2001 Medicare claims data, and to determine whether certain racial and ethnic groups bear a disproportionate burden of urethral stricture disease. Methods We analyzed Medicare claims for fiscal years 1992, 1995, 1998, and 2001. ICD-9 diagnosis codes were used to identify men with urethral stricture. Demographic characteristics assessed included patient age, race, and comorbidities as measured by the Charlson … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
88
0
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 129 publications
(94 citation statements)
references
References 15 publications
1
88
0
5
Order By: Relevance
“…Strictures <1 cm in length respond well to minimally-invasive therapies. 10,11 In one study, strictures with a length <1 cm had a recurrence rate of 27% compared with 50% for those ≥1 cm. 10 Bulbar strictures with a preserved luminal diameter >15 French (5 mm) had the best overall outcomes in a retrospective review of 224 patients who underwent internal urethrotomy.…”
Section: Discussionmentioning
confidence: 99%
“…Strictures <1 cm in length respond well to minimally-invasive therapies. 10,11 In one study, strictures with a length <1 cm had a recurrence rate of 27% compared with 50% for those ≥1 cm. 10 Bulbar strictures with a preserved luminal diameter >15 French (5 mm) had the best overall outcomes in a retrospective review of 224 patients who underwent internal urethrotomy.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 An analysis of Medicare patients in the USA treated for urethral strictures in the period 1992 -2001 showed that urethrotomy comprised 51 -58% of procedures performed, dilatation 35 -44% and urethroplasty only 0.5 -0.8%. 5 The authors pointed out that if the estimated success rate is 95% for urethroplasty and 50% for urethrotomy, the ratio of urethrotomies to urethroplasties performed should be approximately 2:1, and if the success rate of urethrotomy is assumed to be 20%, the ratio should 5:4, much lower than the rates of 10:1 and even 50:1 reported in the literature. 5 Earlier studies suggested that repeated urethrotomy for recurrent urethral strictures may serve to 'stabilise' the stricture, thereby increasing the cumulative success rate.…”
mentioning
confidence: 97%
“…5 The authors pointed out that if the estimated success rate is 95% for urethroplasty and 50% for urethrotomy, the ratio of urethrotomies to urethroplasties performed should be approximately 2:1, and if the success rate of urethrotomy is assumed to be 20%, the ratio should 5:4, much lower than the rates of 10:1 and even 50:1 reported in the literature. 5 Earlier studies suggested that repeated urethrotomy for recurrent urethral strictures may serve to 'stabilise' the stricture, thereby increasing the cumulative success rate. 6,7 However, since the early 1980s some authors have reported that a second urethrotomy had a lower success rate and that repeated urethrotomy did not improve the cumulative success rate.…”
mentioning
confidence: 97%
“…Посттравматические стриктуры отличаются в первую очередь тем, что края «разве-денной» уретры обычно не изменены, и после удаления разде-ляющей их рубцовой ткани и наложения анастомоза заживают без образования стриктур [7]. Стриктуры воспалительные (не превышают 1% всех стриктур), особенно на фоне венерических возбудителей, и с каждым годом имеют всё меньшую роль [8].…”
unclassified
“…Следует помнить, что примерно каждый третий пациент со стриктурой мочеиспускательного канала страдает сахарным диабетом, или иными сопутствующими заболеваниями, требу-ющими обязательной коррекции до, во время и после пластики для достижения успеха от оперативного лечения [8].…”
unclassified